Colour blind test using Ishihara method / Nor Haryati Azali - Azali, Nor Haryati (Faculty of Computer and Mathematical Sciences, 2005)
The "Colour Blind Test Using Ishihara Method" can be used as a tool to help diagnose some eye diseases at an early stage. Colour vision was assessed using Ishihara plates as efficient screening plates for congenital for red-green defects. This application is developing by using Macromedia Director MX and Flash MX and it implement multimedia elements to make it easy to use compared with clinically colour vision test. The interest of developing this application is to bring a new dimension of approach in delivering the information for children to understand the special needs of colour deficient person. Instead of that, the colour blind test application needs to build to help diagnose some eye diseases at an early stage. This report discusses the implementation and finding of "Colour Blind Test Using Ishihara test" as a new approach in interactive multimedia. In addition, the design of this project is to develop a colour blind system for children to test types of colour based on identified colour, number and shape. All subjects passed the Ishihara test, showing that none had a congenital red-green defect and subject who are made fewer than two errors on the plates were considered normal.